PEMANFAATAN ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN KOMPETENSI SDM DAN EFEKTIVITAS PELAYANAN PUBLIK. - Maulidza Nur Fauzi; Imtinan Widhah Kumala; Mohamad Fahmi Yusuf; Tri Winarsih; Siti Musarofah; Bayu Malikhul Askhar; Cahya Intan Syafinaz (Universitas Kadiri, 2026)
Village apparatus in Glagah District, Lamongan Regency, still relies on conventional administrative methods due to limited digital literacy and minimal training on emerging technologies, creating a gap between rising public service expectations and staff competency. This community service activity aimed to enhance village officials' understanding and practical skills in utilizing Artificial Intelligence (AI) to support administrative tasks and public services. The program was implemented through four stages: needs assessment, socialization and training, hands-on mentoring, and evaluation with sustainability monitoring, involving 47 participants from various village positions. Results showed a significant increase in participant comprehension, with average pre-test to post-test scores rising by 43.5 points, alongside concrete outputs such as AI-assisted document drafts and a practical usage guide. Participant satisfaction toward sustainable AI adoption was notably high. This activity concludes that structured, contextual training combined with personal mentoring effectively bridges digital competency gaps and fosters a more adaptive, technology-responsive work culture among village apparatus.